Glossopharyngeal Dystonia Secondary to a Lurasidone-Fluoxetine CYP-3A4 Interaction - Sean Paul; Brian K. Cooke; Mathew Nguyen (Case Reports in Psychiatry)
Acute dystonic reactions are becoming much less prevalent in clinical practice due to the use of newer antipsychotics. Drug-drug interactions, patient characteristics, and environmental and genetic factors all contribute to the rate of occurrence of acute dystonia with second generation agents. In this case, we report a glossopharyngeal dystonia secondary to a lurasidone-fluoxetine CYP-3A4 interaction to highlight the importance of maintaining an index of suspicion for laryngeal dystonia, a potentially fatal dystonia.